Students’ disposition towards computational thinking: a systematic literature review - Saralah Sovey,; Mohd Effendi @ Ewan Mohd Matore, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Computational Thinking (CT) transforms life into something greater than you could have ever imagined yourself living since Industry 4.0 optimizes the computerization of Industry 3.0. Most of the attention on embedding CT during the past decade has focused on the integration of CT skills, which involves investigating students’ programming or computing skills and designing tools to teach and assess CT with only little concern about their disposition, perception, feeling, or attitude towards the application of CT in problem solving across various disciplines or specifically in daily life. Attitude and disposition reflect students’ inclination towards learning CT and reflect their ability to think intelligently about issues confronting them. Hence, this study systematically reviewed how disposition and attitude towards CT have been assessed in the literature of computational thinking. The PRISMA stages of planning, conducting, and reporting the review are phases being applied. This article resulted in three main themes: cognitive, affective, and behavioural components of disposition in CT using SCOPUS and Web of Science (WoS) databases. These three themes produced a total of 17 meaningful sub-themes. This review identifies current research gaps and future directions to conceptualize and assess CT disposition, and the findings are expected to be beneficial for researchers, curriculum designers, and students. In the future, researchers are recommended to develop and validate instruments to measure students’ attitudes and dispositions towards CT rather than simply adapting traditional assessments, as CT is a new thinking tool that varies in conceptualization and operationalization as well.